2019
DOI: 10.1186/s13021-019-0124-x
|View full text |Cite|
|
Sign up to set email alerts
|

Building houses and managing lawns could limit yard soil carbon for centuries

Abstract: Background: Comparisons of soil carbon (C) pools across land uses can be confounded by site-specific history. To better quantify the response of soil C pools to residential development and use, we compared yard soils (n = 20) to adjacent mown fields and second-growth forests within land-use clusters (LUC; n = 12). Land uses within clusters shared site-specific legacies (land use and other soil forming history) prior to residential development (15-227 years ago). We analyzed soil cores to 60-cm depth for carbon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 100 publications
(142 reference statements)
0
2
0
Order By: Relevance
“…Drying and rewetting has been shown to negatively impact DNRA compared denitrification, likely due to DNRA bacteria being more sensitive to fluctuating O 2 levels (Rahman et al., 2019). Additionally, soil mixing/compaction and mowing can cause a long‐term drop in soil C stocks (Peach et al., 2019), which may further limit DNRA (e.g., Hardison et al., 2015). In this case, ditch vegetation management practices such as mowing may favor N removal over retention.…”
Section: Discussionmentioning
confidence: 99%
“…Drying and rewetting has been shown to negatively impact DNRA compared denitrification, likely due to DNRA bacteria being more sensitive to fluctuating O 2 levels (Rahman et al., 2019). Additionally, soil mixing/compaction and mowing can cause a long‐term drop in soil C stocks (Peach et al., 2019), which may further limit DNRA (e.g., Hardison et al., 2015). In this case, ditch vegetation management practices such as mowing may favor N removal over retention.…”
Section: Discussionmentioning
confidence: 99%
“…The South Prong drainage basin includes more open land, saw palmetto fields, mature citrus groves, and limited residential-commercial property relative to much more turfgrass and impervious surfaces in Crane Creek. Previous studies have found a lower reservoir of organic matter in residential lawns because thin (<20 cm) layers of turfgrass often cover soil amended by importing C-and N-poor, sand (Peach et al, 2019). This turfgrass scenario was common in our study area.…”
Section: Concentrations and Fluxes Of Nitrogen And Phosphorus Speciesmentioning
confidence: 71%